Multimodality imaging workup of classical Hodgkin lymphoma in an 8-month-old child - Maad Galal, MD; Nader Ashraf Fawzy, MD; Areez Shafqat, MD; Hirdah Tauqir Rana, MD; Aljohara Aljabr, MD (Radiology Case Reports, 2023)
The incidence of Hodgkin lymphoma (HL) varies by age, most commonly affecting 15-19-year-olds. Cases in children less than 3 years old are exceedingly rare. We report a case of classical HL in an 8-month-old male; the youngest case reported thus far in the literature to our knowledge. Furthermore, while lymphadenopathy is a salient feature of HL, it was absent in our patient, who presented with immunodeficiency and delays in achieving neurologic milestones. A thorough radiologic workup demonstrated bilateral paravertebral masses, collapse of the T3 vertebrae, and severe spinal cord compression. Involvement of the lung, liver, and spleen was also noted. Histopathological evaluation of the paravertebral mass revealed a diagnosis of classical HL. Various non-neoplastic and malignant disorders, such as tuberculosis, Langerhans cell histiocytosis, leukemia, and neuroblastoma, amongst others, could be included in the differential diagnosis of our patient. Using an Illustrative case report, we review the multimodality imaging workup of Hodgkin lymphoma.